Egg consumption and cardiovascular risk: a dose–response meta-analysis of prospective cohort studies - Godos, Justyna (Eur J Nutr, 2020)
PURPOSE: Cardiovascular disease (CVD) is a leading cause of mortality globally and is strongly influenced by dietary risk factors. The aim was to assess the association between egg consumption and risk of CVD risk/mortality, including coronary heart disease (CHD), stroke, and heart failure. METHODS: MEDLINE, Embase, and Web of Science databases were searched through April 2020 for prospective studies. Two independent reviewers screened and extracted the data through standardized methods. Size effects were calculated as summary relative risks (SRRs) in a dose–response fashion through random-effects meta-analyses. RESULTS: Thirty-nine studies including nearly 2 million individuals and 85,053 CHD, 25,103 stroke, 7536 heart failure, and 147,124 CVD cases were included. The summary analysis including 17 datasets from 14 studies conducted on CVD (incidence and/or mortality) showed that intake of up to six eggs per week is inversely associated with CVD events, when compared to no consumption [for four eggs per week, SRR = 0.95 (95% CI: 0.90; 1.00)]; a decreased risk of CVD incidence was observed for consumption of up to one egg per day [SRR = 0.94 (95% CI: 0.89; 0.99)]. The summary analysis for CHD incidence/mortality including 24 datasets from 16 studies showed a decreased risk up to two eggs per week [(SRR = 0.96 (95% CI: 0.91; 1.00)]. No associations were retrieved with risk of stroke. The summary analysis for heart failure risk including six datasets from four studies showed that intake of one egg per day was associated with increased risk raising for higher intakes compared to no consumption [for 1 egg per day, SRR = 1.15 (95% CI:1.02; 1.30)]. After considering GRADE criteria for strength of the evidence, it was rated low for all outcomes but stroke, for which it was moderate (yet referring to no risk). CONCLUSION: There is no conclusive evidence on the role of egg in CVD risk, despite the fact that higher quality studies are warranted to obtain stronger evidence for a possible protection of CVD associated with moderate weekly egg consumption compared to no intake; equally, future studies may strengthen the evidence for increased heart failure risk associated with high regular egg consumption. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00394-020-02345-7) contains supplementary material, which is available to authorized users.